Pharmacokinetics of apixaban in patients with end stage renal disease on hemodialysis and atrial fibrillation: results from the RENAL-AF trial. (25th November 2020) - Pokorney, S; Garonzik, S; Chertow, G.M; Washam, J.B; Mussina, K; Bansal, N; Gadegbeku, C; Garcia, D; Lopes, R.D; Mahaffey, K.W; Middleton, J; Thadhani, R; et al.
Abstract: Background/Introduction: Apixaban use is increasing for stroke prevention in patients with atrial fibrillation (AF) and end stage renal disease (ESRD) on hemodialysis. There is uncertainty as to the optimal dose in this population in part related to the limited available pharmacokinetic (PK) data. Purpose: We comprehensively evaluated the PK of apixaban collected over 1 month of apixaban dosing in 63 patients with AF and ESRD on hemodialysis. Methods: Patients with AF and ESRD on hemodialysis were randomized to warfarin versus apixaban within the RENAL-AF trial with 5 mg BID dosing, except for 2.5 mg BID in those age ≥80 years or weight ≤60 kg. The 5 mg BID dose could be reduced to 2.5mg BID for minor bleeding. Day 1 PK data was collected on all patients pre- and post-hemodialysis. Day 3 and 1 month pre- and post-hemodialysis PK samples were collected in 49 patients. The timing of apixaban dosing and hemodialysis relative to PK samples was recorded. Dosing history, hemodialysis, and PK samples were chronologically integrated with patient specific data such as body size, age, race and gender. This dataset was combined with the ARISTOTLE dataset, and the published PK model from ARISTOTLE describing exposures in the AF population was updated to incorporate an additional clearance term for hemodialysis. The model estimated apixaban exposures (AUC) in RENAL-AF were compared to ARISTOLTE AUC values. Results: There were 285 PK concentrations collected among 63 patients in the RENAL-AF trial. Patients had median age 69 years with 41% women (N=26) and a median weight of 84 kg (49, 157). The median AUCs for patients with ESRD on hemodialysis were 5, 452 and 2, 990 for patients treated with 5mg BID and 2.5mg BID doses, respectively. The median AUCs for patients treated with 5mg BID from ARISTOTLE increased from 2, 802 for patients with class 1 CKD to 5, 863 for class 4 CKD, while they increased from 2, 392 for class 1 CKD to 2, 881 for class 4 CKD in patients treated with 2.5mg BID. The median AUC for patients with ESRD on hemodialysis were within 50% of the exposure of patients from ARISTOTLE for all classes of CKD for the 2.5mg BID dose and for classes 2, 3A, 3B, and 4 CKD for the 5mg BID dose (Figure). Conclusions: The steady state apixaban exposure data in patients with AF and ESRD on hemodialysis were modestly higher but consistent with the results of non-ESRD patients from ARISTOTLE, using 5 mg BID unless patients had age ≥80 years or weight ≤60 kg. Additional clinical outcomes data on the use of apixaban in patients with AF and ESRD on hemodialysis are needed. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Investigator sponsored grant from Bristol-Myers Squibb and Pfizer